Managing educational change in the ICT discipline at the tertiary education level. - Koppi, Tony; Naghdy, Fazel (Australian Learning and Teaching Council, 2009)
This report on the Australian Learning and Teaching Council Information and Communications Technology (ICT) Project is a scoping study in ICT higher education. The core focus is the university curriculum and its perceived relevance among ICT stakeholders. The primary ICT stakeholders include high schools, university staff, students, employers, the community, professional bodies, graduates in the workforce and government. The broad range of stakeholders and rapidly changing circumstances require dynamic and responsive high school and university curricula that balance a range of demands. ICT academic staff, ICT graduates currently in the workforce, and employers of ICT graduates were consulted for this project. [Executive summary, ed]